Burckhardt.Renaissance: Erkundungen und Relektüren eines Klassikers - Beyer, Andreas; Burghartz, Susanna; Burkart, Lucas (Wallstein Verlag, 2021)
On the occasion of Burckhardt's 200th birthday, historians, art historians and cultural scientists gathered in Basel in 2018 to ask about the topicality of his work based on his essay "The Culture of the Renaissance in Italy" (1860), which still sets standards today. The result is a reader that encourages readers to continue reading one of the most influential academic legacies, both critically and appreciatively
Seite 191: Für Hilfe und Unterstützung bei der Durchführung der internationalen Tagung, deren Ergebnisse hier versammelt sind, ... Die Tagung im Mai 2018 wurde vom Rektorat der Universität Basel und der Freiwilligen Akademischen Gesellschaft (FAG), Basel finanziell unterstützt
Keywords: Burckhardt, Jacob -- 1818-1897 -- Congresses; Burckhardt, Jacob -- 1818-1897 -- Cultur der Renaissance in Italien -- Congresses; Burckhardt, Jacob - 1818-1897; Cultur der Renaissance in Italien (Burckhardt, Jacob); Konferenzschrift -- 2018 -- Basel; Burckhardt, Jacob / Die Kultur der Renaissance in Italien; Burckhardt, Jacob